Challenges Of Dormitory Students in ImprovingForeign Language Skills at Uin Syahada Padangsidimpuan - Nesmi Yuli Hasibuan; Fitri Rahma Dini; Ihda Safitri Nasution; Riyani Siregar; Sandi Pradana (SocioSphere: Interdisciplinary Journal of Social Sciences and Humanities, 2025)
This study aims to identify and analyze the challenges faced by UIN Syahada Padang Sidimpuan dormitory students in improving their foreign language skills, especially English and Arabic as flagship programs. In addition, this study also explores the adaptation strategies used by students to overcome these challenges. Through a qualitative case study approach involving in-depth interviews and participatory observation, this study explores students' subjective experiences related to environmental constraints, motivation, access to resources, and social interaction in the context of foreign language learning in a dormitory environment. The findings show that the main challenges faced by dormitory children include the lack of an active foreign language environment, lack of supporting facilities such as books and interactive learning media, weak motivation to study independently, and limited guidance from the campus and dormitory management. In addition, differences in educational background and basic language skills are also inhibiting factors. This study recommends the need for the formation of a language community in the dormitory, the training of peer tutors, and the procurement of a routine foreign language coaching program that is integrated with dormitory activities. With the right strategy, the dormitory environment can be a potential forum for improving students' foreign language skills. The results of the research are expected to provide in-depth insights for universities and dorm managers in designing more effective interventions to support the development of students in foreign languages, which ultimately contributes to improving the quality of graduates at the international level.